Physiotherapeutic techniques and combined therapies for the treatment of knee osteoarthritis (Research, Society and Development, 2023)
The present work aims to describe the main methodologies that contribute to the prevention and treatment of gonarthrosis. The present study is a narrative review of the literature, which aims to examine and synthesize the available literature on treatments used in knee osteoarthritis – gonarthrosis. Until a few decades ago, the treatment of osteoarthritis, also known as gonarthrosis when it affects the knees, was limited to approaches such as the use of simple analgesics, anti-inflammatories, physical measures such as weight loss, muscle strengthening and physiotherapy, in addition to corticosteroid injections. In the most serious cases, the only option was surgical treatment. Several non-pharmacological therapies are used to treat knee osteoarthritis. Among them, the following stand out: acupuncture, manual therapy, physiotherapy, devices (orthotics, shoes, walkers), weight loss, electrotherapy (TENS, ultrasound and laser) and thermal modalities such as cryotherapy, thermotherapy and hydrotherapy. In conclusion, knee osteoarthritis (KOA) is a complex condition that involves degeneration of articular cartilage, changes in the bones, muscles and ligaments that stabilize the knee joint. Conservative treatment plays a fundamental role in the management of KOA, aiming to alleviate pain and improve the patient's function and quality of life.